Social Media Impacts among Students - Ghori, Shaheer Ahmed; Saleem, Usama; Shahbaz, Tahreem (Advances in Social Sciences Research Journal, 2019)
As we see how social media seems to be a very popular platform among the students nowadays and it gains popularity in a very short time. Almost every student have a social media account. Nowadays everyone is busy with their mobile phones. Is social media really helping the students? Our primary purpose is to find the impact of social media growth on the students. We choose a sample of 100 students by random sampling and we use the questionnaire as a data collection instrument. We receive all the questionnaire from the students and apply descriptive statistics to analyze the data. The results have shown the different impacts of social media platforms on students some are positive but most are negative. The results also show social media addiction towards students. The reason why students mostly use social media and how much students use social media in a day.